Relationship between Abducens Nerve Palsy and Local Hematoma in a Case Series of Ruptured Vertebral Artery Dissecting Aneurysm - Shunsaku, Goto (Asian J Neurosurg, 2018)
BACKGROUND: Abducens nerve palsy associated with subarachnoid hemorrhage (SAH) has rarely been reported. Its frequency, mechanism of palsy, association with aneurysmal location, and clinical course are poorly described. The purpose of our study was to evaluate patients with abducens nerve palsy caused by SAH occurring from ruptured vertebral artery (VA) dissecting aneurysm and to find aneurysmal location using initial computed tomography (CT) and its association with clinically detected cranial nerve palsy. METHODS: Fourteen patients of SAH due to ruptured VA dissecting aneurysm were treated at our hospital from January 2011 to May 2015. The clinical courses and CT findings were reviewed retrospectively. RESULTS: Abducens nerve palsy was observed in 77.8% of cases after excluding patients with decreased levels of consciousness. Clots within the prepontine cistern were significantly thicker in cases of VA dissecting aneurysm than in case of supratentorial aneurysm (P = 0.002). CONCLUSION: The findings of our study indicated that ruptured VA dissecting aneurysms, even in cases of angio-negative SAH, are likely to present with abducens nerve palsy.